PENGARUH MEDIA YOUTUBE DALAM PEMBELAJARAN BAHASA INDONESIA ABAD KE-21 - Bernadeta Maharani Sitanggang; Chaira Salsabila; Dina Tahara; Diva Putri Shalied; Khaira Putri Andini; Farel Olva Zuve (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology in the 21st century requires Indonesian language learning to adapt to more interactive media, one of which is YouTube. The problem examined in this study is how the use of YouTube affects the process and results of Indonesian language learning in schools. This study aims to describe the role of YouTube in improving students' language skills, learning motivation, and digital literacy. The method used is a descriptive qualitative approach through interviews with Indonesian language teachers and literature review. The results show that YouTube can increase student engagement, support listening, speaking, reading, and writing skills, and encourage creativity through multimodal projects. However, the use of technology also poses challenges related to the authenticity of student work in the AI era. Therefore, teachers need to act as facilitators who guide the critical and responsible use of digital media. This study recommends the targeted integration of YouTube into the curriculum to strengthen 21st-century Indonesian language learning.